HUACA AZNAPUQUIO: NEW DATA ON HUMAN OCCUPATION, WATER RESOURCES AND ETHNIC TERRITORY IN THE LOWER CHILLON BASIN - Espinoza Pajuelo, Pedro (2008)
The Huaca Aznapuquio Archaeological Delimitation Project, directed by the first author on October 2007, has provided legal and technical basis to protect this site and new data about the historical processes in the lower Chillon Valley during late prehispanic times. In that sense, this paper describes the general results of the project about the occupational sequence in association to the Aznapuquio wetland, the architectonical structures partially exposed for our excavations and the presence of Ichma and Inca ceramic style. Finally, we discuss about the characteristics of the Late Horizon in the valley, the water resources prehistoric management and the archaeological indicators of Colli ethnic territory.